2018
DOI: 10.1111/jam.13743
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin induces Metarhizium spp. to produce conidia with elevated tolerance to UV ‐B, and upregulates photolyases, laccases and polyketide synthases genes

Abstract: The enhanced UV-B tolerance of Metarhizium spp. conidia produced on Rb-enriched media may improve the effectiveness of these fungi in biological control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 82 publications
0
21
1
7
Order By: Relevance
“…ns = not significant. commonly used in biological control (Braga et al, 2001(Braga et al, , 2015Paixão et al, 2017;Pereira-Junior et al, 2018;Bernardo et al, 2020). Conidia from Metarhizium species exposed to UV-B radiation (irradiances between 920 and 1,200 mW m −2 ) had both germination and survival affected in a dose-and time-dependent manner (Braga et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…ns = not significant. commonly used in biological control (Braga et al, 2001(Braga et al, , 2015Paixão et al, 2017;Pereira-Junior et al, 2018;Bernardo et al, 2020). Conidia from Metarhizium species exposed to UV-B radiation (irradiances between 920 and 1,200 mW m −2 ) had both germination and survival affected in a dose-and time-dependent manner (Braga et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Riboflavin and sodium nitrate are already used for media supplementation of entomopathogenic fungi (Iwanicki et al 2020 ), but there are no reports of these components alone and their influence on the thermotolerance of the fungus. Pereira-Junior et al ( 2018 ) demonstrated that supplementation of BDA medium with riboflavin increased expression of photolyase, laccase, and polyketide synthase genes in M. robertsii ARSEF 2575. Thus, just as the presence of riboflavin in BDA induced the expression of components that increase tolerance to UV radiation, the presence of riboflavin in rice may induced fungal proteins production.…”
Section: Discussionmentioning
confidence: 99%
“…Riboflavin, in turn, acts as a cofactor of FMN and FAD molecules, molecules that are essential for redox homeostasis, protein folding, DNA repair, β-oxidation of fatty acids, and amino acid oxidation (Liu et al 2020 ). Thus, the presence of riboflavin in the culture medium could favor fungal thermotolerance, as well as induced tolerance to UV radiation (Pereira-Junior et al 2018 ), by the increase of proteins responsible for cell repair. In addition to intracellular proteins, possible extracellular components contributing to heat tolerance, since riboflavin increased the expression of genes involved in conidia pigmentation and therefore radiation tolerance (Pereira-Junior et al 2018 ; Lovett and St. Leger 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations